TET2 exon 2 skipping is an independent favorable prognostic factor for cytogenetically normal acute myelogenous leukemia (AML): TET2 exon 2 skipping in AML. (May 2017) - Mohamed, Aminetou Mint; Balsat, Marie; Koering, Catherine; Maucort-Boulch, Delphine; Boissel, Nicolas; Payen-Gay, Lea; Cheok, Meyling; Mortada, Hussein; Auboeuf, Didier; Pinatel, Christiane; El-Hamri, Mohamed; Tigaud, Isabelle; et al.
Highlights: The prognosis of many patients with AML remains uncertain yet the optimal post-remission therapy for such patients is unclear. TET2 exon 2 skipping (TET2E2S) has been identified in AML cells. We hypothesize that TET2E2S may serve as biomarker for outcomes in AML. TET2E2S was found associated with a reduced relapse rate and prolonged survival. Assessment of TET2 exon 2 splicing status might improve AML risk stratification. Abstract: In AML, approximately one-third of expressed genes are abnormally spliced, including aberrant TET2 exon 2 expression. In a discovery cohort (n = 99), TET2 exon 2 skipping (TET2E2S) was found positively associated with a significant reduction in the cumulative incidence of relapse (CIR). Age, cytogenetics, and TET2E2S were independent prognostic factors for disease-free survival (DFS), and favorable effects on outcomes predominated in cytogenetic normal (CN)-AML and younger patients. Using the same cutoff in a validation cohort of 86 CN-AML patients, TET2E2S high patients were found to be younger than TET2 low patients without a difference in the rate of complete remission. However, TET2E2S high patients exhibited a significantly lower CIR (p < 10 −4 ). TET2E2S and FLT3-ITD, but not age or NPM1 mutation status were independent prognostic factors for DFS and event-free survival (EFS), while TET2E2S was the sole prognostic factor that we identified for overall survival (OS). In both the intermediate-1 and favorable ELN genetic categories, TET2E2S remained significantly associated with prolonged survival. There was no correlation between TET2E2S status and outcomes in 34 additional AML patients who were unfit for IC. Therefore our results suggest that assessments of TET2 exon 2 splicing status might improve risk stratification in CN-AML patients treated with IC.